Energy system interaction during basketball exercise simulation in junior elite players - Hoos, O.; Latzel, R.; Stier, S.; Kaufmann, S.; Fresz, V.; Reim, D.; Beneke, R. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The Basketball Exercise Simulation Test (BEST) has been proposed as a novel match-simulating fitness test for elite basketball players showing both discriminative and longitudinal validity (Scanlan et al., 2012). However, the energetic profile of the BEST is not known. Therefore the aim of this study was to assess the energetic profile of the BEST in junior elite basketball players. Methods: 10 male elite junior basketball players (age: 15.5±0.6y, height: 180±9cm, weight: 66.1±11.2kg) performed a modified BEST (20 circuits on half-court ( 1348m) consisting of jumping, sprinting, jogging, shuffling action and short breaks; Scanlan et al., 2012) simulating a 10min quarter of FIBA Europe basketball play. Besides circuit time (C in s), sprint time (S in s) and sprint decrement (SD in %), VO2 (in ml/kg/min), heart rate (HR in bpm) and blood lactate concentration (blc in mmol/l) were obtained. Metabolic energy and power above rest (Wtot in kJ, Ptot in Watt/kg) as well as energy share (in kJ, %) were calculated from oxygen uptake during exercise (Waer, aerobic component), net lactate production (Wblc, lactic component) and the fast component of post-exercise oxygen uptake kinetics (Wpcr, alactic component) (Beneke et al., 2004). Interrelations between metabolic energy estimates and performance measures were assessed by linear regression. Results: BEST performances (C: 21.29±1.17s, S: 1.65±0.13s, SD: 11.9±4.2%) elicited peak values of VO2, HR, BLC of 57.6±3.7ml/kg/min, 202±9bpm, 10.3±2.1mmol/l, respectively. Wtot of 761.0±168.4kJ and Ptot of 19.3±1.6Watt/kg were supplied by a Waer of 673.3±144.1kJ (89±2%), a Wblc of 38.7±13.2kJ (5±1%) and a Wpcr of 49.0±16.5kJ (6±1%), respectively. Assuming an aerobic replenishment of pcr energy stores during short breaks (8-10s) between circuits (Beneke et al., 2004), the adjusted energy share during BEST yielded Waer: 66±4%, Wblc: 5±1% and Wpcr: 29±1%. In a stepwise linear regression model Waer explained 54% of variance in S, while Wblc and Wpcr did not further enhance the model. Discussion: Consistent with general findings on energy system interaction during maximal exercise (Gastin et al., 2001) our data shows that the intermittent profile of junior elite basketball simulated by BEST primarily relies on aerobic energy. Additionally, a substantial repetitive alactic energy contribution seems to be present. These findings should be considered when basketball specific training programs are designed.